The Mediating Role of Anthropometric Improvements in The Effects of Resistance Training on Speed, Strength, and Power in U20 Futsal Athletes - Asmara, Mirza; Prasetyo, Yudik; Suhartini, Bernadeta; Pamungkas, Gallant; Shodiq, Burhaan (Physical Education Theory and Methodology, 2025)
Background. Adolescence is characterized by heightened trainability, yet approximately 18 % of young people are overweight or obese. It has been noted that in five Yogyakarta futsal clubs, 37–51 % of U17 players show BMI ≥ 25 kg·m⁻², potentially hampering performance. Objectives. This study aimed to examine whether implementing an eight‑week resistance‑training programme enhances 20‑m sprint speed, lower‑body strength, and explosive power in U17 futsal athletes, and whether body fat change mediates these effects. Materials and methods. Thirty 18-19‑year‑old male players completed periodised resistance sessions that were conducted on a thrice-weekly basis. Body mass, BMI, body fat percentage (BF %), sprint time, one‑repetition‑maximum leg press, and standing long‑jump distance were measured in the pre‑/post‑intervention phase. Paired‑sample t‑tests were used to assess within‑group changes. Mediation models (PROCESS; 5,000 bootstraps) examined whether ΔBF % transmitted the influence of ΔBMI on performance. Results. A substantial decrease was observed in body mass (–1.21 kg), BMI (–0.43 kg·m⁻²), and BF % (–1.48 %), while sprint time (–0.95 s), leg‑press strength (+11.9 kg), and jump distance (+11.8 cm) improved (all p < .001). ΔBMI predicted ΔBF % (B = 5.38, p < .001). BF % partially mediated the BMI–sprint link (indirect effect = 3.52, 95 % CI [2.70, 4.47]), although a significant direct path persisted. Mediation was non‑significant for strength and power; BMI reduction showed no relation to strength change, yet retained a strong direct association with power gains independent of BF %. Conclusions. The findings of this study indicate that resistance training markedly improves neuromuscular performance and body composition in youth futsal athletes. A lower BMI enhances sprint speed both directly and through concurrent reductions in BF %, whereas adaptations in strength and power arise through mechanisms other than adiposity. Training programmes should therefore combine neuromuscular loading with strategies for healthy weight management to optimise youth futsal performance.